All Mixed Together at Once: An Analysis of the Structure of the Novel El gato de sí mismo, by Uriel Quesada - Rojas González, José Pablo (2014)
This paper seeks to study –from the theoretical contributions of Mikhail Bakhtin– the structure of Uriel Quesada's novel, El gato de sí mismo. The article seeks to characterize this Costa Rican literary work within the genre novel –specifically as polyphonic novel–. This definition of Quesada's novel is based on the coexistence of other literary subgenres and on the lack of monologic unity, as noted by the Russian theorist.